2018
DOI: 10.1002/ijc.31409
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of human papillomavirus vaccination for different populations: A modeling study

Abstract: International variations in the prevalence of HPV infection derive from differences in sexual behaviors, which are also a key factor of the basic reproductive number (R0) of HPV infection in different populations. R 0 affects the strength of herd protection and hence the impact of a vaccination program. Similar vaccination programs may therefore generate different levels of impact depending upon the population's pre‐vaccination HPV prevalence. We used IARC's transmission model to estimate (i) the overall effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…The results are therefore not representative of the general Dutch population, probably underestimating the impact of vaccination. 20 The decrease in the HPV16/18 prevalence among women in our study, coincided with an increase in the percentage of women who reported to be vaccinated. After adjustment for vaccination status, the HPV16/18 prevalence did not differ in 2015 as compared to 2009, indicating that the increasing proportion of vaccinated women explained the decreasing HPV prevalence.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…The results are therefore not representative of the general Dutch population, probably underestimating the impact of vaccination. 20 The decrease in the HPV16/18 prevalence among women in our study, coincided with an increase in the percentage of women who reported to be vaccinated. After adjustment for vaccination status, the HPV16/18 prevalence did not differ in 2015 as compared to 2009, indicating that the increasing proportion of vaccinated women explained the decreasing HPV prevalence.…”
Section: Discussionsupporting
confidence: 64%
“…Last, we used a population of visitors to STI clinics who are at higher HPV risk as compared to the general population. The results are therefore not representative of the general Dutch population, probably underestimating the impact of vaccination …”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Through the implementation of screening methods (including pap-smear and HPV DNA testing), most pre-neoplastic lesions were detected and treated before the onset of invasive cancer, thus reducing the burden of cervical cancer [ 3 ]. Interestingly, the recent adoption of primary prevention (i.e., vaccination) aims to eradicate HPV and HPV-related lesions [ 4 ]. Modeling studies showed that the widespread adoption of vaccination would reduce the incidence of HPV related lesions, dramatically [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%